Scaling up Smart-Valleys approach for land and water development in inland valleys in Mali - Djagba, Justin. F; Kone, Pierre; Doumbia, Salif; Dossou-Yovo, E. R (2024)
This report outlines the scaling-up efforts of the Smart-Valleys approach under the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project in Mali. Focusing on sustainable land and water development in inland valleys, the initiative has expanded to 40 sites across 24 villages in the Sikasso, Koulikoro, and Segou regions, directly benefiting 1953 farmers, of whom 58% are women. The report highlights the collaborative efforts between AfricaRice and the National Institute of Rural Economy (IER) in capacity building, field demonstrations, and farmer engagement. The adoption of Smart-Valleys has improved water management, enhanced rice yields, and strengthened the resilience of agricultural systems, showcasing the potential of Smart-Valleys as a transformative tool for sustainable development in Mali.